The Potential Synergy of Halal Industry and Islamic Banking in Bangka Belitung Province: SWOT Analysis - Hendra Cipta; Hatamar Hatamar (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
The synergy between the halal industry and sharia banking is essential to creating a halal ecosystem in Bangka Belitung Province. Meanwhile, this synergy has not been seen at this time. This qualitative research was conducted through a SWOT analysis to answer the causes of the lack of synergy between Islamic banking and the halal industry. The findings of this research show that the strength of this synergy is the majority Muslim population and religious harmony, abundant natural resources. The weakness of this synergy is that national regulations are not evenly distributed to support the halal ecosystem, and there are many obstacles to the development of Islamic banking. In terms of opportunities, this synergy can be seen in the rapid development of financial technology, the many types of halal industry businesses giving many options for Islamic banks to make financing products. Meanwhile, on the threat, this synergy is constrained by the low level of public literacy.